O regime jurídico de proteção à intimidade na era da informação: da tutela da personalidade ao tratamento dos dados pessoais - Pimenta, Rafael da Cunha (2021)
The vicissitudes of the contemporary world of legal practitioners have an increasingly dynamic posture in the face of the social reality that is imposed on them. This evolutionary aspect is inseparable from Legal Science and reveals, even more forcefully, in an era marked by technology. This new paradigm stems from the fact that, in the context of the information society and Big Data, intersubjective relationships take on new contours, for whose proper delineation it seems relevant to resume the ontological essence of the human being and its dual condition of subject and object of rights, an end that it is possible to better support any extension of your personality. Based on such premises, it starts with the dogmatic construction of personality rights and theories relating to private life and intimacy, in order to delimit an individual legal sphere of the human being. Then, the analysis of the normative content of the dignity of the human person is carried out, from which it becomes possible to investigate the hermeneutic scope of the fundamental rights related to the protection of personal data, based on a gravitational constitutional paradigm, the in order to emphasize the centrality of the Fundamental Law in the legal system. The objective of this study, therefore, is to present a basic core of personal data protection from the structuring of the concept of intimacy as a fundamental individual right, demonstrating. Therefore, an essentially qualitative approach to the proposed theme was carried out, without neglecting, however, the hermeneutic analysis required by the scope of the work. With the priority use of the deductive method, bibliographic research was adopted as the main technical procedure used. Despite being related to the relatively recent theme and still controversial in several aspects, especially for the legal field, it is clear that, given the current economic model based, also on the exploration of the personal information of individuals, as well as considering the potential practical implications underlying this scenario, it is understood that the proposed theme is a matter of considerable legal and social relevance.